The impact of Arabic school Manuscripts Paintings on Timurid school one's as the fundamental source of both concept of composition and visual elements development - Hany Mohamed Mohamed Sabry (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
This research deals with the impact of the Arabic school of Manuscripts Paintings on The Timurid school as the main source of the development of composition and Artistic elements, a comparative analytical descriptive study, and the research start with a quick presentation of the methods and features of the three schools of Painting, the Arabic School through Mughal school and its artistic features, followed by the presentation of the artistic methods of the Timurid school and its Artistic characteristics, Followed By An analysis of 9 Sample each Sample contains more than one Miniature from the Arabic and Timurid school, The eighth last Sample Containing a designs from the Arabic, Mongolian and Timurid school depicting the same subject and showing in these sample the way of the development and processing of forms and artistic elements in the three Painting schools, the works were analyzed and extracted similarities between the designs, whether similarities in composition in general or in the subject or similarities between the Artistic elements as well as similarities in the movements of lines and artistic style and the distribution of elements, and the research ends with many results specific to the Artistic and philosophical aspect and the results show the extent to which the Arabic Painting School influences Timurid Manuscripts Painting, including the transfer of lines and artistic methods. Some specific elements such as. the movements and conditions of people in many cases, and the closure of the scenes in similar ways